PENGARUH MOTIVASI GURU TERHADAP HASIL BELAJAR HAFALAN AL-QUR’AN PADA SISWA KELAS VII DI SMP IT MUHAMMADIYAH MIRI SRAGEN TAHUN PELAJARAN 2024/2025 - Fitri Handayani; Suhadi Suhadi; Yetty Faridatul Ulfah (STKIP Pesisir Selatan, 2025)
This study examines the influence of teacher-provided motivation on the Qur’an memorization learning outcomes of seventh-grade students at Muhammadiyah Integrated Islamic Junior High School (SMP IT) in Sragen. The background of the study is the crucial role of teachers in fostering students’ learning motivation, particularly in a Qur’an memorization (tahfidz) program where some students have not met the memorization targets set by the school. Previous research shows that students’ learning motivation is positively correlated with academic achievement. However, few have specifically investigated the role of teachers’ external motivation on Qur’anic memorization achievement. This correlational quantitative research involved 30 seventh-grade students as the sample. Data on teacher motivation were collected through questionnaires, while memorization outcomes were obtained from tahfidz exam scores. The results indicate that teachers’ motivational efforts in class are in the good to very good category, and students’ Qur’an memorization outcomes are generally good (the majority of students achieved the fluency and accuracy targets). Nevertheless, Pearson product-moment correlation analysis showed no significant influence of teacher motivation on memorization outcomes (r = 0.101; p > 0.05), with an extremely weak relationship. This finding suggests that teacher-provided motivation alone is not sufficient to significantly improve memorization results.